Kepribadian Narsistik dan Perilaku Hate Comment Pengguna Media Sosial - Cantika Nindita; Ranadya Candra Kirana; Mira Nurfitri Fesenrey; Lusy Trianggraini; Ridwan Siskandar; Hana Lestari (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
Narcissistic personalities are often encountered in social media, where this narcissistic personality does not escape from hate comments. Narcissistic personality itself is a feeling of self-love that is excessive or not in accordance with its normal level of self-love. This condition triggers hate comment behavior in which some individuals feel dislike, disagree with, or envy someone with a narcissistic personality. The purpose of this study was to determine the relation between narcissistic personality and hate comments on social media. The research subjects were 146 people aged 14-25 years who were active in social media. The data collection method used a narcissistic personality scale and hate comment behavior scale which was adapted from previous questionnaires. The scale model is 8 in Likert form with 5 levels. Using correlation and regression data analysis techniques, it was found that 11.3% of the influence of narcissistic personality on hate comment behavior on social media was found. Furthermore, based on the results of a simple regression test, an equation model shows that hate comment behavior on social media can be explained positively by narcissistic personality. Thus, the higher the narcissistic personality, the higher the hate comment behavior.